Β-Glucan exacerbates allergic airway responses to house dust mite allergen. Issue 1 (December 2016) - Hadebe, Sabelo; Kirstein, Frank; Fierens, Kaat; Redelinghuys, Pierre; Murray, Graeme; Williams, David; Lambrecht, Bart; Brombacher, Frank; Brown, Gordon
Abstract β-(1, 3)-Glucan is present in mould cell walls and frequently detected in house dust mite (HDM) faeces. β-Glucan exposure is thought to be associated with pulmonary allergic inflammation in mouse and man, although the published data are inconsistent. Here, we show that highly purified β-glucan exacerbates HDM-induced eosinophilic, T helper 2 type airway responses by acting as an adjuvant, promoting activation, proliferation and polarisation of HDM-specific T cells (1-Derβ T cells). We therefore provide definitive evidence that β-glucan can influence allergic pulmonary inflammation.